Do Cell-Cycle Phase–Specific Markers Predict Disease Grade, Stage, and Outcome in Cervical Carcinoma?. Issue 6 (July 2015) - Kuku, Stephanie; Proctor, Ian; Loddo, Marco; Kadalayil, Latha; KhoshZaban, Mohammed; Ledermann, Jonathan; McCormack, Mary
<x xml:space="preserve">Abstract</x> Aims Multiparameter analysis of cell cycle markers has shown a strong relationship between cell cycle progression and tumor grade, stage, and clinical outcome in penile, renal, ovarian, and breast cancers. We sought to link expression of cell cycle phase–specific markers in cervical cancer to tumor grade, stage, and clinical outcome to investigate their potential use as prognostic and predictive markers. Methods Pretreatment biopsy material was obtained from 35 patients with cervical cancer (stage IB2-IVA) and 12 normal cervix control cases. Each patient was treated with neoadjuvant chemotherapy followed by chemoradiation. Immunohistochemical staining was performed using a panel of cell cycle phase markers: replication licensing factors: Mcm2 (minichromosome maintenance 2) and geminin, and the standard proliferation marker Ki67 (clone MIB-1). Results The expression levels of each cell cycle biomarker were very high in all cases of squamous cell carcinoma of the cervix regardless of grade or stage of disease. In our cohort, all cases displayed an aggressive, so-called actively cycling phenotype. Univariate analysis showed that none of the cell cycle biomarkers predicted grade, stage, or clinical outcome. Conclusions Cell cycle phase–specific markers do not appear to predict disease grade, stage, or outcome in our sample of patients with cervical cancer. This is not surprising, given that the expression of each cell cycle biomarker was very high in all cases. Indeed, all the cases of squamous cell carcinoma of the cervix (n = 28) and all but 1 of the adenocarcinomas (n = 7) in this study displayed an aggressive "actively cycling" phenotype. This predominance of actively cycling tumors is unusual and may reflect the viral etiology underlying the disease. These preliminary findings raise many interesting questions including the prognostic value of disease grade and markers of proliferation in cervical tumors as reliable prognostic indicators. Further work on a larger cohort of patients is warranted.